AMT (ACHIEVEMENT MOTIVATIONTRAINING) SEBUAH RANCANGAN INTERVENSI UNTUK MENINGKATKAN EFIKASI DIRI PADA MAHASISWA PROGRAM KHUSUS ULAMA IAIN ANTASARI BANJARMASIN (Studi Eksperimen) - Mulyani, Mulyani; Mubarak, Mubarak; Hairina, Yulia (Faculty of Ushuluddin and Humanities, 2015)
Belief or self efficacy is owned by someone to do an action influences activities and efforts of someone in facingÂ difficulty of finishing of certain assignment. Especially, college students who are in Program Khusus Ulama inÂ IAIN Antasari, they need to have a belief with theirselves to finish the final assignment as a schedule decided.Â With this reason, to increase the self efficacy this study designed an Achievement Motivation Training (AMT).Â It is a training oriented to increase motivation to achieve some goals had have decided by individuals based onÂ their ability. The research subject invited to know theirselves more through self evaluation based on other peopleÂ assessment. Then, deciding some goals wants to reach and deciding a strategy and a target based on their abilityÂ achieved from result of self evaluation. Sample of this research was 10 people and to decide experimentÂ participation by random sampling. This training was for college students of Program Khusus Ulama of TafsirÂ Hadis department in Faculty of Ushuluddin and Humaniora. The conclusion is that Achievement MotivationÂ Training (AMT) has effects to increase self efficacy of ollege students of Program Khusus Ulama. The scoreÂ of Self Efficacy showed that studentsâ self efficacy proven higher than before they follow the AMT.